Molecular Detection and Characterization of New Emerging Viruses by PCR Analysis in Hatay and Tekirdag Vineyards - Hamide Deniz Kocabağ; Kadriye Çağlayan; Mona Gazel (Turkish Journal of Agriculture: Food Science and Technology)
The improvements on the next generation sequencing or high-trough output technologies allowed the discovery of several unknown viruses in grapevines and also in other plants . The most important new emerging grapevine viruses were identified as Grapevine pinot gris virus (GPGV), Grapevine syrah virus 1 (GSyV-1), Grapevine red blotch-associated virus (GRBaV) and Grapevine roditis leaf discoloration virus (GRLDaV). The aim of the present study was to investigate the occurrence and characterization of these viruses in Tekirdag and Hatay viticulture production areas by PCR and DNA sequencing analyses. Totally 191 and 111 grapevine samples showing both virus-like symptoms and symptomless were collected from Tekirdağ and Hatay provinces, respectively. Among the tested samples GPGV and GSyV-1 were detected in both local and imported cultivars by the infection rate of 43.62 % and 1.04% in Tekirdağ , respectively. In Hatay provice, only GSyV-1 was detected by the infection rate of 0.9 % and all tested samples were negative for GPGV, GRBaV, GRLDaV. RT-PCR results showed that DNA fragments of 411 bp, 302 bp and 618 bp corresponding to the part of the coat protein (CP), movement protein (MP) and the replicase genes of GPGV were successfully amplified in Tekirdağ samples. All PCR products of GPGV were directly sequenced on both strands. All the nucleotide sequences of CP, MP and 5’ UTR and N-terminus of replicase genes shared the highest sequence identity with different GPGV isolates deposited in Genbank